Low MicroRNA-126 Levels in Right Ventricular Endomyocardial Biopsies Coincide With Cardiac Allograft Vasculopathy in Heart Transplant Patients. Issue 5 (May 2020) - Heggermont, Ward A.; Delrue, Leen; Dierickx, Karen; Dierckx, Riet; Verstreken, Sofie; Goethals, Marc; Bartunek, Jozef; Vanderheyden, Marc
Abstract : Background: Endothelium-enriched microRNAs (miRs) are involved in the development of cardiac allograft vasculopathy (CAV). Recently, serum-derived miR-126-3p and -5p, known endothelial microRNAs with a crucial function in angiogenesis and re-endothelialization, provided additional predictive power for cardiac allograft vasculopathy in addition to clinical predictors. However, their myocardial expression in and relationship with CAV are still unknown. Our study aim was to investigate the expression of endomyocardial microRNA-126-3p and microRNA-126-5p levels in heart transplant recipients and their relationship with allograft vasculopathy. Methods: We studied 39 heart transplant recipients, 21 with proven allograft vasculopathy (CAV+) and 18 without allograft vasculopathy (CAV−) with serial coronary angiograms. Additionally, 8 patients with end-stage native coronary artery disease (CAD) were added to the study to investigate disease specificity of the microRNA signature. The mRNA levels of miR-126-3p and miR-126-5p were determined by qRT-PCR in the right ventricular endomyocardial biopsies obtained at baseline and during routine follow-up. Results: MiR-126-3p levels were significantly lower in the CAV+ group compared to the CAV− group at follow-up, while miR-126-5p levels were unaltered. This was in stark contrast to native CAD patients in whom miR-126-3p and -5p levels were significantly higher. qPCR levels of miR-126 targets are differentially regulated in CAV versus ischemic cardiomyopathy and are influenced by the administration of immunosuppressive agents in endothelial cells. Conclusions: Our data provide evidence for a distinct microRNA signature in heart transplantation patients with allograft vasculopathy. In contrast to CAD patients, lower miR-126-3p levels coincide with the development of cardiac allograft vasculopathy. Further studies in a larger patient population are warranted to determine if the serial measurement of myocardial microRNA-126 products could help in risk assessment and early detection of CAV. Abstract : Supplemental Digital Content is available in the text.